Development of large-scale microalgae production in the Middle East. (January 2022) - Hirayama, Akihiko; Sueyoshi, Mark N.; Nakano, Takashi; Ota, Yuki; Kurita, Hiroyuki; Tasaki, Masaharu; Kuroiwa, Yoichi; Kato, Takahiro; Serizawa, Sadayoshi; Kojima, Keisuke; Al-Maamari, Rashid S.; Hasegawa, Takeshi; et al.
Graphical abstract: Abstract: Microalgae in the Middle East can theoretically address food security without competing for arable land, but concerns exist around scalability and durability of production systems under the extreme heat. Large-scale Chlorella sorokiniana production was developed in outdoor raceway ponds in Oman and monitored for 2 years to gather data for commercial production. Biological and technical challenges included construction, indoor/outdoor preculturing, upscaling, relating productivity to water temperature and meteorological conditions, harvesting, drying, and quality control. Small cultivation systems required cooling for initial scale-up, but, despite maximum temperatures of 49.7 °C, water temperatures were at acceptable levels by evaporative cooling in larger raceway ponds. Contamination with Vampirovibrio chlorellavorus was identified by 16S rDNA amplicon sequencing and addressed by culture replacement. Productivities ranged from 8 to 30 g-dry weight m -2 d -1, with estimated annual productivity of 16 g-dry weight m -2 d -1 as functions of solar intensity and water temperature, confirming that the region is suitable for commercial microalgae production.